2021
DOI: 10.1039/d1sm00291k
|View full text |Cite
|
Sign up to set email alerts
|

Elastic modulus distribution in poly(N-isopopylacrylamide) and oligo(ethylene glycol methacrylate)-based microgels studied by AFM

Abstract: The spatial elastic modulus distribution of microgel networks in presence and absence of bifunctional crosslinkers is studied by AFM. Thermoresponsive poly(N-isopopylacrylamide) (PNIPAM) and poly(2-(2-methoxyethoxy)ethyl methacrylate-co-oligo(ethylene glycol) methacrylate)) (P(MEO2MA-co-OEGMA)) microgel are...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…While E was highest in the center, it decreased laterally towards the periphery by one order of magnitude. 68 This trend has even been observed in the collapsed state above VPTT, where microgels in solution are actually homogeneous. 45,52 Stiffness tomography measurements have revealed that the stiffness is an intricate function of the position within the network (Fig.…”
Section: The Role Of the Interfacementioning
confidence: 83%
“…While E was highest in the center, it decreased laterally towards the periphery by one order of magnitude. 68 This trend has even been observed in the collapsed state above VPTT, where microgels in solution are actually homogeneous. 45,52 Stiffness tomography measurements have revealed that the stiffness is an intricate function of the position within the network (Fig.…”
Section: The Role Of the Interfacementioning
confidence: 83%
“…This is due to the lower diffusion and lower reactivity of the bulkier OEGMA monomers compared to the smaller comonomers MEO 2 MA and ManEAM. 16 Furthermore, the proposed POEGMA-rich segments have a higher LCST compared to segments where MEO 2 MA is present in larger amounts. 48 Therefore, these microgels are not fully collapsed at 37 °C as seen from the swelling curve (Figure 1).…”
Section: Man Density and Architecture Control Bacteria Binding And Re...mentioning
confidence: 89%
“…This is to be expected since the addition of a crosslinker leads to more compact networks, and previous work showed that P(OEGMA-co-MEO2MA) microgels are stiffer and denser compared to PNIPAM microgels for similar crosslinker concentrations. 16 When increasing the temperature above the VPTT, the increased deformability of self-crosslinked microgels enables a large increase in Man density, up to 50-fold, whereas the microgels with an additional crosslinker showed only a 4-fold increase in Man density. This explains the E. coli release for the self-crosslinked microgels below VPTT, which was not seen for PNIPAM BIS -Man.…”
Section: Man Density and Architecture Control Bacteria Binding And Re...mentioning
confidence: 99%
See 2 more Smart Citations